Graduating Nursing Students' Empowerment and Related Factors: Comparative Study in Six European Countries - Visiers-Jiménez, Laura; Kuokkanen, Liisa; Leino-Kilpi, Helena; Löyttyniemi, Eliisa; Turjamaa, Riitta; Brugnolli, Anna; Gaspar, Filomena; Nemcová, Jana; Palese, Alvisa; Rua, Marília; Zelenikova, Renata; Kajander-Unkuri, Satu (Healthcare (Basel, Switzerland), 2022)
New nurses are needed in healthcare. To meet the role expectations of a registered nurse, nursing students must feel empowered at graduation. However, there are only a few studies focusing on nursing students' empowerment. This study aims to describe and analyze graduating nursing students' level of empowerment in six European countries and potential related factors. A comparative and cross-sectional study was performed in the Czech Republic, Finland, Italy, Portugal, Slovakia, and Spain with graduating nursing students (n = 1746) using the Essential Elements of Nurse Empowerment scale. Potentially related factors included age, gender, a previous degree in health care, work experience in health care, graduation to first-choice profession, intention to leave the nursing profession, level of study achievements, satisfaction with the current nursing programme, clinical practicums, theoretical education, and generic competence measured with the Nurse Competence Scale. The data were analysed statistically. Graduating nursing students' self-assessed level of empowerment was moderate, with statistical differences between countries. Those with high empowerment had no intention to leave the nursing profession, had a higher level of study achievements, and a higher self-assessed generic competence level. The results suggest that empowerment needs to be enhanced during nursing education. Further research is needed to understand the development of empowerment during the early years of a nursing career.
Keywords: empowerment; competence; nursing students; intention to leave; nursing education